2005
DOI: 10.1021/ja051840m
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Quinoidal Oligothiophenes with Dicyanomethylene Groups at Terminal Positions as Highly Amphoteric Redox Molecules

Abstract: A series of highly extensive quinoidal oligothiophenes carrying a dicyanomethylene group at both terminal positions is synthesized. As the quinoidal structures extend, they have highly amphoteric abilities and show strong electronic absorptions in the visible to near-infrared region. The higher homologues, quinquethiophene and sexithiophene, exist as equilibrium mixtures with the biradical species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
182
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(199 citation statements)
references
References 19 publications
7
182
0
3
Order By: Relevance
“…From the ESR signal intensity, the fractions of magnetic species were estimated to be 2.8% for 28 and 29% for 29. 44 The species that gave ESR signals would be thermally excited triplet species, because triplet populations estimated from the theoretical ¦E ST (10.9 kJ mol ¹1 for 28, 5.65 kJ mol for 29) and a Boltzmann distribution are 3.6% for 28 and 24% for 29. Singlet biradical contribution to the ground state was investigated by using Raman spectroscopy.…”
Section: ¹1mentioning
confidence: 99%
“…From the ESR signal intensity, the fractions of magnetic species were estimated to be 2.8% for 28 and 29% for 29. 44 The species that gave ESR signals would be thermally excited triplet species, because triplet populations estimated from the theoretical ¦E ST (10.9 kJ mol ¹1 for 28, 5.65 kJ mol for 29) and a Boltzmann distribution are 3.6% for 28 and 24% for 29. Singlet biradical contribution to the ground state was investigated by using Raman spectroscopy.…”
Section: ¹1mentioning
confidence: 99%
“…[53,59] Alternatively, alkane side chains can be used to chemically modify the molecule, greatly facilitating the solubility of organic materials. [117] However, it should be noted that intermolecular interactions in the solid state or intermolecular orbital overlap, determining the ability of electron transport, could not be offset by additional solubilizing side groups. [46] The strategy of combining the p-electron-deficient moiety with highly tailorable solubilizing groups has been applied to realize the n-channel small molecules and polymeric materials.…”
Section: Solution Processabilitymentioning
confidence: 99%
“…12,13 Quinoidal oligothiophenes possess positionally locked double bonding between repeat units giving a forced degree of -overlap and high rigidity lacking in traditional oligomers. 13,26,27 Highly planar quinoidal structures with extended conjugation, low bandgap, and amphoteric redox behavior have received great attention in the field of organic electronics. [26][27][28] We showed that in addition to those electronic transport properties quinoidal oligothiophenes demonstrate remarkable nonlinear absorption properties in a very broad spectral range.…”
Section: A Initial Results On Nonlinear Optical Properties Of Quinoimentioning
confidence: 99%
“…13,26,27 Highly planar quinoidal structures with extended conjugation, low bandgap, and amphoteric redox behavior have received great attention in the field of organic electronics. [26][27][28] We showed that in addition to those electronic transport properties quinoidal oligothiophenes demonstrate remarkable nonlinear absorption properties in a very broad spectral range. 12,13 Recent theoretical studies predicted that open-shell systems can demonstrate very strong enhancement of NLO susceptibilities as compared to the traditional closed-shell configurations.…”
Section: A Initial Results On Nonlinear Optical Properties Of Quinoimentioning
confidence: 99%
See 1 more Smart Citation